Synaptic organization of the rat thalamus: a quantitative study - ONAT, FİLİZ; ŞİRVANCI, SERAP (SPRINGER-VERLAG ITALIA SRL, 2011)
First-order thalamic nuclei receive driving afferents from ascending pathways and transmit processed information to the cortex. Higher-order thalamic nuclei receive driver messages from layer 5 of cortex and transmit information from one cortical area to the other. The different types of axon terminals RL (round vesicles, large terminals), RS (round vesicles, small terminals) and F (flattened vesicles) and their synaptic junctions have been here compared in three first-order (ventrobasal, lateral geniculate and anteroventral) and three higher-order (posterior, lateral posterior and mediodorsal) thalamic nuclei of the rat. In the present study, the higher-order relays differ from first-order relays as in the cat, in having fewer driver terminals (RL) and synapses than do the first-order relays. However, the F terminals showed opposite ratios in the first versus higher-order thalamic nuclei. The majority of the terminals in all thalamic nuclei studied were RS terminals. The area measurements of the three types of terminals and synaptic lengths showed no significant differences between first and higher-order nuclei. The driver inputs represent the minority and the modulatory inputs represent the majority of the terminals and synapses in all thalamic nuclei. In conclusion, there is a relative paucity of driver inputs, whereas modulatory inputs establish more numerous synapses to achieve finer modulation.
Keywords: GABA immunostaining; Electron microscopy; Drivers; Modulators; LATERAL GENICULATE-NUCLEUS; HIGHER-ORDER; CORTICOTHALAMIC PROJECTIONS; RETICULAR NUCLEUS; PHA-L; CORTICOCORTICAL COMMUNICATION; GABAERGIC INTERNEURONS; SOMATOSENSORY THALAMUS; RELATIVE DISTRIBUTION; ANTEROGRADE TRACER